(untitled) (Universal International Scientific Journal, 2026)
. This article analyzes the problems associated with the quality of education in the process of introducing digital technologies into the modern education system. The study highlights the role of digital technologies in the educational process, their impact on pedagogical activity, and their potential for increasing educational efficiency. It also substantiates the importance of the human factor in the educational process and the need to develop the digital competence of teachers.